The Expenditure of Vietnamese Families in Recent Years - Binh, Nguyen Thanh (Richtmann Publishing, 2011)
In our daily life, we need certain expenses to ensure the survival and development of ourselves. These expenses can consist ofdaily food buying, medicine or education, etc., as well as direct investment into production to create income sources for individuals andfamilies, other expenses on creating and maintaining social relationships as expenses on special ceremonies like weddings or funerals, etc.In addition, there are expenses on buying houses, equipment and household facilities. Thus, how is the reality of Vietnamese households’expenses at current time? Based on the statistics from General Statistical Office in Vietnam in the period 2002-2008, we see that theaverage expense of Vietnamese households was significantly improved in recent years. Average monthly expense of households headed bywomen is higher than that of households headed by men. Average expense gap between urban and rural areas have decreased slightly butremained large differences of the expense rate. Nationally, the biggest expense of all the households is living expense and this rate tendedto decrease year by year. The rate of living expense in urban areas was always higher than rural areas from 2002 to 2008 and theinequality of quintile 5 (the richest) and quintile 1 (the poorest) in monthly per capita average living expense is clearly shown. It can besaid that with daily expenses, women have the highest right of deciding, most men do not take part in this duty. With other expenses likechildren’s education and disease treatment, men play higher role in deciding. In buying expensive things, the rate of both wives andhusbands discussing on making decisions ranks highest.